Liver and Nutrition. An Optimal Diet for Non-Alcoholic Fatty Liver Disease - M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. This review study is aimed at characterizing the nutrition of patients with non-alcoholic fatty liver disease (NAFLD).General findings. A high-calorie diet, followed even for a short period of time, can lead to an increase in the lipid content in hepatocytes and an increase in ALT values. These changes occur much earlier than weight gain, glucose metabolism disorders and other clinically obvious changes. So far, only the Mediterranean diet (or the Mediterranean type of food) has been scientifically confirmed as beneficial for human health. It is recommended for patients with NAFLD both by Russian and international clinical guidelines. The molecular mechanisms of beneficial effects on human health have been confirmed for such Mediterranean diet components as polyphenols, carotenoids, oleic acid, polyunsaturated fatty acids and dietary fiber. The enrichment of the Mediterranean diet with olive oil (+10 g) reduces the risk of diabetes mellitus by 40 %. The addition of Omega-3 fatty acids to food reduces the risk of hepatocellular cancer. A balanced ratio of omega 3 and omega 6 in the diet is more important than the absolute amount of individual fatty acids. Vegetables and fruit contain two main classes of antioxidants: polyphenols and carotenoids. In patients with NAFLD, they exhibit an anti-inflammatory and antifibrotic effect both in vivo and in vitro. Food produced from whole grain has a lower energy potential as compared to that produced from refined grain. Meat contains various nutrients, such as proteins, iron, zinc, B12 vitamin, as well as sodium, saturated fatty acids and cholesterol, which serve as risk factors for the development of NAFLD and other cardio-metabolic disorders. In this paper, we present a clinical observation of a 51-year-old patient with NAFLD and cardio-metabolic disorders. Practical recommendations are given on changes in his lifestyle and the choice of optimal therapy with the application of multifunctional drugs affecting all disease aspects.Conclusion. The concepts of ‘correct or healthy’ nutrition and ‘lifestyle modification’ are increasingly attracting much attention both in terms of the prevention and treatment of liver diseases. Proper nutrition is important for a good life prognosis in patients with non-alcoholic fatty liver disease (NAFLD).